The Impact of Plasmodium Berghei Exposure In-utero on Neurobehavioral Profile in Mice - Akhabue Keneth Okojie; Khalid Rauf; Eghosa Iyare (Basic and Clinical Neuroscience, 2019)
Introduction: The World Health Organization estimates that about 25 million pregnant mothers are currently at risk for malaria, and that malaria accounts for over 10,000 maternal and 200,000 neonatal deaths per year. The current hypothesis of early life programming supports the premise that many developmental delay and disorders may have their origin In-utero. Therefore, the current study aimed at evaluating the possible impact of experimental malaria exposure In-utero on neurobehavioral profile in mice offspring. Methods: Pregnant mice were intraperitoneally infected on gestational day 13 with 1.02×105 infected red blood cells. Pregnant mice (both infected and uninfected) were allowed to deliver and the offspring were monitored up to postnatal day 42 when anxiety-like, Obsessive-Compulsive Disorder (OCD), and locomotor activity were evaluated using elevated plus maze, marble burying, and Open Field Test, respectively. Results: The current study showed that maternal infection with Plasmodium berghei resulted in an interesting behavior in offspring characterized by increased anxiety-like and OCD behaviors. Locomotor activity was however not affected. Conclusion: It may be concluded that In-utero exposure to experimental malaria in mice causes behavioral changes.